Retracted: Gut Microbiome Signatures of Risk and Prodromal Markers of Parkinson Disease. Issue 2 (15th June 2020) - Heinzel, Sebastian; Aho, Velma T. E.; Suenkel, Ulrike; von Thaler, Anna‐Katharina; Schulte, Claudia; Deuschle, Christian; Paulin, Lars; Hantunen, Sari; Brockmann, Kathrin; Eschweiler, Gerhard W.; Maetzler, Walter; Berg, Daniela; et al.
Abstract : Retraction: Heinzel, S. et al., Gut Microbiome Signatures of Risk and Prodromal Markers of Parkinson Disease, Annals of Neurology 2020, 88(2), 320‐331 (https://onlinelibrary.wiley.com/doi/10.1002/ana.25788 ). The above article, published online on May 22, 2020 in Wiley Online Library (wileyonlinelibrary.com), has been retracted by agreement between the authors, the journal Editor in Chief Clifford B. Saper, MD, PhD, and Wiley Periodicals LLC. The retraction has been agreed due to an unintentional extensive misuse of the term "physical activity" instead of "physical inactivity" throughout the paper. The errors have been corrected for clarity and republished here: https://doi.org/10.1002/ana.26128 .